Representasi Aktivitas Petani Teh Pada Kemeja - Bella Serlia; Widdiyanti Widdiyanti; Wisnu Prastawa (Institut Seni Indonesia Padangpanjang, 2022)
Kerinci is one of the tea-producing areas, especially Kayu Aro area..Besides as tea plantations area it is also a tourist attraction that is visited by many tourists because of its natural beauty and the cool air. The concept of the creation of this work departs from the activities of tea farmers and tea plants, the activities of tea farmers are realized in sequence starting from hoeing, fertilizing, picking tea leaves, pruning, to drying tea leaves. Moreover, the craftsmen also added the tea plant motifs such as leaves, twigs, and flowers that have been sterilized. The theoretical foundations used in realizing this work are: form, function, color, stillization, and aesthetics. The method in the process of creating this work starts from the exploration stage, then continues at the design stage then the creation of the work. This work uses a written batik technique using primisima cloth and reactive dyes. The work that was created in the form of shirts was as many as seven, including four in the form of designs and three finished works.